Public policies and start-ups in Malaysia: New firms under the Ninth Malaysia Plan / Low Pau Chin - Low , Pau Chin (2018)
Small and medium-sized enterprises (SMEs) have long been recognized as major contributors to economic development of a country. State intervention in the economy to nurture SMEs has long been a public policy feature in industrialized East Asian states such as Japan, South Korea and Taiwan. Studies dealing with this issue assess state intervention in the economy from the perspective of developmental state theory, building on the work of Chalmers Johnson who assessed the rapid industrialization of Japan’s economy. Johnson emphasized the important role played by the state in promulgating policies for private enterprise development, in terms of their growth, productivity and competitiveness, for the purpose of maintaining economic development. In Malaysia, the government’s aspirations to develop SMEs has been reinforced in its five-year Malaysia Development Plans (MDPs). Generally, the objectives of the MDPs were concurrent with those of the New Economic Policy (NEP), an affirmative action plan introduced in 1970 that aspired to restructure wealth, particularly through the development of ethnic Malay entrepreneurs within the business community. When Abdullah Ahmad Badawi became Prime Minister of Malaysia on 31 October 2003, he persisted with the developmentalist model but with a focus on aiding SMEs, including start-ups, specifically as a means to nurture domestic entrepreneurship through his Ninth Malaysia Plan, implemented between 2005 and 2010. However, there are no studies analyzing the links between start-ups and the implementation of government policies, as well as the effectiveness of assistance programmes under the Malaysia Plans, and the 9MP, in particular. While new businesses are viewed as a major contributor to economic development, the reality is that many start-ups cannot survive the infancy stage. According to Malaysian government figures, the business failure rate of start-ups has increased from 22% in 2006 to 50% in 2010, even though the government had introduced numerous institutions, policies and incentives through its 9MP to ensure the longevity of these enterprises. Recognizing the severe repercussions of business failures to the development of a country’s economy, a key question arises: why have government policies and incentives to develop start-ups not been effective? This study examines the factors contributing to the sustainability of start-ups, including through different forms of state intervention.